Disease Prevalence and Snail Predation Associated with Swell-Generated Damage on the Threatened Coral, Acropora palmata (Lamarck) - Bright, Allan J.; Rogers, Caroline S.; Brandt, Marilyn E.; Muller, Erinn; Smith, Tyler B. (Frontiers in Marine Science, 2016)
Disturbances such as tropical storms cause coral mortality and reduce coral cover as a direct result of physical damage. Storms can be one of the most important disturbances in coral reef ecosystems, and it is crucial to understand their long-term impacts on coral populations. The primary objective of this study was to determine trends in disease prevalence and snail predation on damaged and undamaged colonies of the threatened coral species, Acropora palmata, following an episode of heavy ocean swells in the US Virgin Islands (USVI). At three sites on St. Thomas and St. John, colonies of A. palmata were surveyed monthly over one year following a series of large swells in March 2008 that fragmented 30 to 93% of colonies on monitored reefs. Post-disturbance surveys conducted from April 2008 through March 2009 showed that swell-generated damage to A. palmata caused negative indirect effects that compounded the initial direct effects of physical disturbance. During the 12 months after the swell event, white pox disease prevalence was 41% higher for colonies that sustained damage from the swells than for undamaged colonies (df = 207, p = 0.01) with greatest differences in disease prevalence occurring during warm water months. In addition, the corallivorous snail, Coralliophila abbreviata, was 46% more abundant on damaged corals than undamaged corals during the 12 months after the swell event (df = 207, p = 0.006).